2000
DOI: 10.1056/nejm200008033430504
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Inhaled Corticosteroids and the Prevention of Death from Asthma

Abstract: The regular use of low-dose inhaled corticosteroids is associated with a decreased risk of death from asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
446
0
30

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,010 publications
(483 citation statements)
references
References 24 publications
7
446
0
30
Order By: Relevance
“…It has been reported that the regular use of ICS and a good compliance is associated with a decreased risk of death and hospitalization owing to asthma [21, 22], as well as with fewer asthma attacks [23]. In our multivariate analysis, the regular use of medication and the self-reported compliance were positively associated with the absence of asthma attacks, even if the association was not statistically significant and the strength of the association was definitely lower than that related to an adequate dosage of anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the regular use of ICS and a good compliance is associated with a decreased risk of death and hospitalization owing to asthma [21, 22], as well as with fewer asthma attacks [23]. In our multivariate analysis, the regular use of medication and the self-reported compliance were positively associated with the absence of asthma attacks, even if the association was not statistically significant and the strength of the association was definitely lower than that related to an adequate dosage of anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The commencement of ICS treatment at a very early stage of asthma can reduce the risk of a later decline in lung function [4]. Regular ICS treatment is effective in preventing the worsening of symptoms, asthma-related deaths and hospitalization; this efficacy is long lasting [5,6]. A long-term study of adult asthma, which lasted 15 years, from 1976 to 1994 (a period before the widespread use of ICS treatment), showed that the forced expiratory volume (FEV) decreased by 38 ml/year in asthmatics and by 22 ml/year in non-asthmatics [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a large community study, the risk of dying of asthma was lower for patients who were dispensed four or more low-dose corticosteroid inhalers per year compared with those who received none. 7 In a large randomised controlled trial, the risk of serious exacerbations (emergency department visits, hospitalisations, death) was also halved and symptoms were significantly reduced with regular use of budesonide 400 micrograms/day, even in patients with symptoms as infrequent as once a week or less.…”
Section: Inhaled Corticosteroids Are Very Effectivelow Dose and Afformentioning
confidence: 99%